Inteksi famili x lokasi pada uji keturunan generasi kedua acacia mangium di sumatera dan kalimantan - Teguh Setyaji (Jurnal Pemuliaan Tanaman Hutan, 2013)
The study was conducted to investigate the existence of  family × site  interactions observed in  second generation  open-pollinated progeny test  of  Acacia mangium in two locations: Lipatkain, Riau (Sumatra) and  Kenangan, East Kalimantan.  The progeny tests were  established   using  51-55 families  originated  from Oriomo River Papua New Guinea  provenance. There were 31common families tested at the both sites. Growth on both sites was significantly different between families. The average  height  and diameter was 15,9 m and  13,3 cm  respectively at  Kenangan, and  17,0 m and  16,6 cm  respectively at  Lipatkain. Family × site interactions  were  highly significant for height and diameter. The ratio of variance component of interaction to the family variance component (s2fl / s2f ) for  diameter (1,6) and height (1,2) were largerr than  Shelbourne’s  critical value (0,5),    indicating the low   genotypic stability at family level for the both traits  where the  diameter was  more sensitive than height to changing  site conditions. Genetic correlations between the same trait at different sites were low:  0.45 for height  and 0.38 for diameter. The greatest genetic gain and relative efficiency of family selection were generally expected from selecting and planting families in the same site.